(E)-N '-(2,4-Dihydroxybenzylidene)-4-nitrobenzohydrazide - Lair, N.M.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
The title compound, C14H11N3O5, is essentially planar, with an r.m.s. deviation for the non-H atoms of 0.0832 (3) angstrom. In the crystal, O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds link adjacent molecules into layers parallel to (101). These layers are further connected into a three-dimensional network via C-H center dot center dot center dot O interactions. In addition, a pi-pi interaction occurs between the aromatic rings [centroid-centroid distance = 3.5425 (8) angstrom]. An intramolecular O-H center dot center dot center dot N hydrogen bond is also observed.